Broussochalcone A Induces Apoptosis in Human Renal Cancer Cells via ROS Level Elevation and Activation of FOXO3 Signaling Pathway. (27th October 2021) - Lee, Han Ki; Cha, Hyo Sun; Nam, Myeong Jin; Park, Kyungmoon; Yang, Yung-Hun; Lee, Jongsung; Park, See-Hyoung
Abstract : Broussochalcone A (BCA) is a chalcone compound extracted from the cortex of Broussonetiapapyrifera (L.) Ventenat that exerts various effects, such as potent antioxidant, antiplatelet, and anticancer effects. However, the effects of BCA against cancers have been seldom studied. This study is aimed at demonstrating the apoptotic mechanisms of BCA in A498 and ACHN cells, which are two types of human renal cancer cell lines. MTT, cell counting, and colony formation assays indicated that BCA treatment inhibited cell viability and cell growth. Further, cell cycle analysis revealed that BCA induced cell cycle arrest at the G2/M phase. Annexin V/PI staining and TUNEL assays were performed to determine the apoptotic effects and DNA fragmentation after treatment with BCA. Based on western blot analysis, BCA induced the upregulation of cleaved PARP, FOXO3, Bax, p21, p27, p53, phosphorylated p53 (ser15, ser20, and ser46), and active forms of caspase-3, caspase-7, and caspase-9 proteins, but downregulated the proforms of the proteins. The expression levels of pAkt, Bcl-2, and Bcl-xL were also found to be downregulated. Western blot analysis of nuclear fractionation results revealed that BCA induced the nuclear translocation of FOXO3, which might be induced by DNA damage owing to the accumulation of reactive oxygen species (ROS). Elevated intracellular ROS levels were also found following BCA treatment. Furthermore, DNA damage was detected after BCA treatment using a comet assay. The purpose of this study was to elucidate the apoptotic effects of BCA against renal cancer A498 and ACHN cells. Collectively, our study findings revealed that the apoptotic effects of BCA against human renal cancer cells occur via the elevation of ROS level and activation of the FOXO3 signaling pathway.